A method for a fast and economical in situ collection of pore water in sandy sediments - Dutta, Saurav; Saar, Raoul; Lavie, Zach; Vered, Gal; Bradbury, Harold J.; Antler, Gilad (Frontiers in Marine Science, 2022)
Marine sediment represents one of the most significant carbon reservoirs. Extraction of pore water from the uppermost 10 cm of the sediment column, just below the sediment-water interface, in coastal environments can be used to assess the rapid chemical changes caused by extensive subsurface biological and chemical reactions. However, owing to relatively large grain size of the sediment in some shallow coastal environments, sediment and pore water mixes quickly making collection of core samples for pore water extraction extremely difficult. Here, we present a simple method utilizing Rhizons to collect in situ pore water from coastal environments. We conducted both ex situ and in situ experiments, using fluorescein as a tracer, to understand the influence of overlying water during pore water collection through this method. These experiments also allowed us to assess the volume of pore water collected before fluorescein is observed in the samples at different vertical depths within the sediment column. We found that: 1. discarding the initial 2 mL of water minimizes the memory effect, 2. collection of 10 mL of water avoids interference from surrounding pore water and the overlying water column and 3. a vertical resolution of minimum 2 cm could be attained for sediments with grain size of 1 mm and less. We finally present data from two linear transects from different sites in the Gulf of Aqaba. Results from these case studies demonstrate expected patterns of high concentrations of iron and hydrogen sulfide in pore water from the sediment where surface coloration suggested iron and sulfate reduction was dominating, respectively. Both case studies, therefore, independently validated the Rhizon sampler method for collecting pore water in situ from marine sediments in coastal environments.